Opsin gene sequence variation across phylogenetic and population histories in Mysis (Crustacea: Mysida) does not match current light environments or visual-pigment absorbance spectra - Asta Audzijonyte; Pahlberg, J; Viljanen, M; Donner, K; Vainola, R (2012)
The hypothesis that selection on the opsin gene is efficient in tuning vision to the ambient light environment of an organism was assessed in 49 populations of 12 Mysis crustacean species, inhabiting arctic marine waters, coastal littoral habitats, freshwater lakes (‘glacial relicts’) and the deep Caspian Sea. Extensive sequence variation was found within and among taxa, but its patterns did not match expectations based on light environments, spectral sensitivity of the visual pigment measured by microspectrophotometry or the history of species and populations. The main split in the opsin gene tree was between lineages I and II, differing in six amino acids. Lineage I was present in marine and Caspian Sea species and in the North American freshwater Mysis diluviana , whereas lineage II was found in the European and circumarctic fresh- and brackish-water Mysis relicta, Mysis salemaai and Mysis segerstralei . Both lineages were present in some populations of M. salemaai and M. segerstralei . Absorbance spectra of the visual pigment in nine populations of the latter three species showed a dichotomy between lake (λ max = 554–562 nm) and brackish-water (Baltic Sea) populations (λ max = 521–535 nm). Judged by the shape of spectra, this difference was not because of different chromophores (A2 vs. A1), but neither did it coincide with the split in the opsin tree (lineages I/II), species identity or current light environments. In all, adaptive evolution of the opsin gene in Mysis could not be demonstrated, but its sequence variation did not conform to a neutral expectation either, suggesting evolutionary constraints and/or unidentified mechanisms of spectral tuning.